Influence of cement particles on the mechanical and buckling behavior of laminated GFRP composites with variation of end conditions of buckling - Singh V.; Kumar P.; Srivastava V.K. (My University, 2025)
Mechanical behavior of particle-loaded laminated composites depend upon the type of matrix, filler, reinforced fibers and architecture of fibers. Further, buckling behavior of a laminated composite varies with its end conditions, i.e. free-free or fixed-fixed. Failure mechanisms like delamination, debonding and fiber fracture vary with the end conditions of buckling. Presence of hard filler may also change the buckling behavior. Thus, in the present article, the mechanical and buckling behavior of cement loaded woven glass fiber reinforced epoxy matrix composites were investigated. Cement was varied as 1%, 3% and 5% by weight of epoxy. Thickness of composites were also varied as 3.1 mm, 4.4 mm and 6.3 mm by varying the number of reinforced glass fiber mats. Tensile, Izod impact and Vickers micro-hardness tests and, buckling tests under free-free and fixed-fixed conditions were performed to assess the mechanical and buckling behavior respectively. Fractured composites were analyzed under scanning electron microscope (SEM). The results showed that tensile strength decreased and hardness increased with increase in percentage of cement. Composites with minimum thickness showed lowest tensile strength. Critical buckling load increased with increase in thickness of composites for both end conditions. However, the nature of variation of buckling load with the percentage of filler varies for every thickness. SEM images showed that damage of composites mainly involved fiber breakage and delamination. Cement particles were effective in deflecting the advancing crack. © 2018 IOP Publishing Ltd.